Macular Holes: Main Clinical Presentations, Diagnosis, and Therapies. (11th April 2022) - Premi, Elias; Donati, Simone; Azzi, Lorenzo; Porta, Giovanni; Metrangolo, Cristian; Fontanel, Liviana; Morescalchi, Francesco; Azzolini, Claudio
Abstract : Macular holes are a spectrum of retinal diseases that comprehends full-thickness macular holes (FTMHs), refractory/recurrent macular holes, lamellar macular holes (LMHs), myopic macular holes (MMHs), traumatic macular holes, and macular holes secondary to other retinal pathologies or injuries. There are various classifications of the subtypes of macular hole, and only in recent times researchers defined a common nomenclature, especially thanks to the evolution in retinal imaging, offered by new instruments like the swept-source OCT. The proposed therapies for macular holes are different and range from a "wait-and-see" approach to the vitrectomy, with different results in each subtype of macular hole. This narrative review has the purpose to investigate the available evidence in literature to give a summary of the knowledge about these retinal pathologies.